Malignant Peripheral Nerve Sheath Tumor with Rhabdomyoblastic Differentiation: Diagnostic Challenges and Literature Review - Cabeda, Rafaela; Fauth, Bruno Vinícius; Rottenfusser, Robson; Henn, Nicoli Taiana; Brusamarelo, Vitória (Brazilian Journal of Case Reports, 2025)
Malignant Peripheral Nerve Sheath Tumor (MPNST) is a rare sarcoma originating from Schwann cells or pluripotent cells of the neural crest. It accounts for 5–10% of soft tissue sarcomas, with a prevalence of 1:100,000 in the general population. Its etiology may be sporadic, associated with neurofibromatosis type 1 (NF1), or related to prior radiation exposure. Diagnosis is complex and relies on imaging studies complemented by histopathological and immunohistochemical analysis. The ideal treatment is complete surgical resection, while chemotherapy and radiotherapy are reserved for unresectable tumors. Prognosis is generally poor, with a five-year survival rate between 50–60%. We report the case of a 53-year-old female patient who presented with pain, swelling in the left thigh, and an inguinal nodule initially misdiagnosed as an inguinal hernia. A biopsy revealed a spindle cell neoplasm, and the patient was referred for further evaluation. Magnetic resonance imaging revealed an abdominal mass of 361.6 cm³, with peritoneal metastases and pulmonary nodules. Initial immunohistochemical analysis suggested rhabdomyosarcoma, but a subsequent biopsy confirmed the diagnosis of MPNST with rhabdomyoblastic differentiation. The treatment was changed to chemotherapy with doxorubicin and ifosfamide, but the patient showed unfavorable progression and was transitioned to palliative care.